ASSESSING MATHEMATICAL MOTIVATION IN PRIMARY EDUCATION IN EDO STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The focus of this study is to determine the proportion of Nigerian Primary School teachers that use the various assessment instruments in the assessment of pupils in mathematics; the sources from which teachers generate their mathematics test items; the levels of questions set by the teachers on the Bloom’s taxonomy of cognitive domains; the extent to which Primary School teachers validate their test instruments; how the teachers utilise the outcomes  of  the formative  tests  in  schools;  and problems faced  by  the  teachers  in  the assessment processes in primary schools. The research design for this study was the survey research design. One hundred and Fifty primary school teachers were sampled from Edo State of Nigeria through purposive sampling technique. There were made up of 108 females and 42 males. The main instrument used for the data collection was a Mathematics Assessment Construction Scale (MACS) questionnaire designed to elicit responses from the subjects in the areas of assessment instruments, source of test items, levels of cognitive domain covered by the questions, validation and item analyses. Other areas covered are the use of formative tests and problems of assessing pupils in primary school mathematics. The questionnaire consists of 23 questions on a four point likert scale using never, not often, often and very often. The split half method was used to establish a reliability coefficient of 0.79. Simple frequency counts and percentages were used to analyse the data and answer the research questions. Results of the study showed that most of the teachers often written tests(100%) and assignments(88%).Group work(76%) very few of them use observation(30%), oral examination(6%) and peer group assessment(8%);  74%  of  the  teachers  source  their  assessment  questions from  textbook publisher’s questions,  76%   construct their questions and very few  of them  source  their questions from past questions(32%) and question and answer books(30%); most of the teachers set questions covering knowledge(100%), comprehension and application(88%) while only 38% of them set questions on real life problems; 82% of the teachers often carry out content validity of the test instruments and very few  teachers carry out reliability  test(4%), item difficulties(10%) and item discrimination power(24%); most of the teachers give formative test and feedback to pupils while  only 52% of the teachers often give remediation lessons to the pupils. Some of the problems identified include absenteeism, lateness and truancy of pupils, lack of interest by pupils, lack of materials, lack of knowledge about assessment by teachers etc. It was recommended that teachers should be encouraged to use variety of assessment instruments;  teachers should be retrained on  the techniques of  test construction, and be encouraged to set questions on real life problems.